Transformasi Digital Pt Bank Jago Tbk dari Bank Konvensional menjadi Bank Digital - Restiana Ie Tjoe Linggadjaya; Bontor Sitio; Patar Situmorang (STIE-JIC, 2022)
his research is to conduct a study on the Business Strategy Transformation of PT Bank Jago Tbk (Bank Jago); A transformation from a Conventional Bank (previously Bank Artos) to a digital bank, the current Bank Jago. This research carries a relatively new research topic, namely digital transformation at banks in Indonesia. The research population is all digital banks in Indonesia, with a total of 5 digital banks and 7 banks in the process of going digital. However, with the limitations of existing data regarding digital banks, discussions were conducted on Bank Jago from the financial side, five digital transformation domains according to Rogers (2016), and comparative studies of bank performance on a limited basis with Book III bank (of which Bank Jago is one of The Book III banks) and aggregate bank in general. The result of this research is that Bank Jago has carried out the right business strategy in accordance with the five domains of digital transformation according to Rogers (2016), where with digital transformation has achieved better business growth compared to Book III banks and aggregate banks in general. Practical implications: (1) the success of Bank Jago can be used as a role model for other digital banks and conventional banks that want to change the business model through digital transformation, (2) For OJK: make further regulations for digital bank reporting, which is separate from commercial bank reporting so that Indonesian banks have data on the development of digital banks.